2014
DOI: 10.1007/978-3-319-12114-7_12
|View full text |Cite
|
Sign up to set email alerts
|

A Positive Feedback Loop Between Prolactin and Stat5 Promotes Angiogenesis

Abstract: The signal transduction events that orchestrate cellular activities required for angiogenesis remain incompletely understood. We and others recently described that proangiogenic mediators such as fibroblast growth factors can activate members of the signal transducers and activators of transcription (STAT) family. STAT5 activation is necessary and sufficient to induce migration, invasion and tube formation of endothelial cells. STAT5 effects on endothelial cells require the secretion of the prolactin (PRL) fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 135 publications
(162 reference statements)
1
8
0
Order By: Relevance
“…Indeed, acute injection of sRlx-HD augmented plasma levels of Prolactin significantly in WT-NP and CKO-NP mice. Moreover, we could show that sRlx-HD via Prolactin induces activation of the Prolactin major target signalling molecule STAT5 36 in LV tissue. Direct injection of Prolactin activated STAT5 in both genotypes further explaining how sRlx via Prolactin and STAT5 activation could induce cardiomyocyte growth in both genotypes.…”
Section: Discussionmentioning
confidence: 83%
“…Indeed, acute injection of sRlx-HD augmented plasma levels of Prolactin significantly in WT-NP and CKO-NP mice. Moreover, we could show that sRlx-HD via Prolactin induces activation of the Prolactin major target signalling molecule STAT5 36 in LV tissue. Direct injection of Prolactin activated STAT5 in both genotypes further explaining how sRlx via Prolactin and STAT5 activation could induce cardiomyocyte growth in both genotypes.…”
Section: Discussionmentioning
confidence: 83%
“…In COMMD7 silenced HepG2 cells, the inhibition rate of NF-κB was 75%, suggesting that COMMD7 regulates the nuclear translocation of NF-κB and the consequent gene transcriptions involved in HCC growth [10]. However, it was demonstrated that mutational changes in individual proteins can cause fundamental functional changes well beyond the pathway they function in by a positive feedback loop embedded in the crosstalk [1215]. Interestingly, many oncogenes associated with tumor development and progression are activated by NF-κB [1618].…”
Section: Introductionmentioning
confidence: 99%
“…STATs are involved in a series of biological events, including cell differentiation 58 , angiogenesis 59 , innate immunity 60 and cell growth regulation 61 . Numerous studies have demonstrated that STAT3 is mainly expressed in glial cells 62 , 63 and is involved in inflammatory reactions 64 , 65 .…”
Section: Discussionmentioning
confidence: 99%